2011
DOI: 10.1088/0004-637x/743/1/88
|View full text |Cite
|
Sign up to set email alerts
|

Non-Detection of the Putative Substellar Companion to Hd 149382

Abstract: It has been argued that a substellar companion may significantly influence the evolution of the progenitors of sdB stars. Recently, the bright sdB star HD 149382 has been claimed to host a substellar (possibly planetary) companion with a period of 2.391 days. This has important implications for the evolution of the progenitors of sdB stars as well as the source of the UV-excess seen in elliptical galaxies. In order to verify this putative planet, we made 10 radial velocity measurements of HD 149382 over 17 day… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…Although this early result could not be confirmed by other groups (Norris et al 2011), we soon found much better candidates. The selection criteria of the MUCHFUSS project not only single out massive companions but also companions with very low masses in extremely short orbits.…”
Section: Substellar Companionscontrasting
confidence: 71%
“…Although this early result could not be confirmed by other groups (Norris et al 2011), we soon found much better candidates. The selection criteria of the MUCHFUSS project not only single out massive companions but also companions with very low masses in extremely short orbits.…”
Section: Substellar Companionscontrasting
confidence: 71%
“…Although we adopted the rough wavelength calibration used for planet search work, we did not attempt to use this calibration to measure our radial velocities. Rather, we extracted radial velocities in pixel space by crosscorrelating the spectra of our candidate cluster members with those of our observed RV standard stars (a similar pixel-space cross-correlation method was employed by Norris et al (2011)). To reduce the errors introduced by comparing two stars of different spectral types, we paired each candidate member to an RV standard star that minimized the difference between their V − J colors (∆(V − J)), with V − J = 0.8 for the bluest standard star and V − J = 2.4 for the reddest.…”
Section: Radial Velocity Determinationmentioning
confidence: 99%
“…However, the attribution of these signals to exoplanets is debatable (Krzesinski 2015;Blokesz et al 2019). Using the RV method, Geier et al (2009) announced the discovery of a close-in (P orb = 2.4 days) planet of several Jupiter masses around HD 149382, but this was ruled out by high-precision RV measurements obtained with the Hobby-Eberly Telescope spectrograph, which excluded the presence of almost any substellar companion with P orb < 28 days and M sin i 1M Jup (Norris et al 2011).…”
Section: Search For Planets Around Hot Subdwarfs: Current Statusmentioning
confidence: 99%